PENERAPAN MODEL PEMBELAJARAN INQUIRY DISCOVERY DALAM KONTEKS PENDIDIKAN AGAMA ISLAM: PENERAPAN MODEL PEMBELAJARAN INQUIRY DISCOVERY DALAM KONTEKS PENDIDIKAN AGAMA ISLAM - Pertiwi, Rizka; Fahlawi, Sahrizal; Sobri, Muhammad (JURNAL MAHASANTRI, 2024)
Islamic Religious Education (PAI) learning aims to equip students with knowledge, understanding and values originating from Islamic teachings. To achieve optimal results, teachers are expected to be able to develop learning models that support the achievement of learning objectives. One learning model that can be used is the inquiry discovery model, where students are given the opportunity to formulate problems and find answers to these problems. This article aims to explore the application of the inquiry discovery learning model in the context of Islamic religious education (PAI) as well as steps that can be taken by teachers to improve students' thinking abilities. Keywords: Model Pembelajaran, inquiry discovery, Pendidikan Agama Islam.